Pengaruh Sistem Informasi e-PADI terhadap Pembayaran Pajak Bumi dan Bangunan Perdesaan dan Perkotaan di Badan Pendapatan Daerah Kabupaten Deli Serdang - Sarah Vika Sabrina; Vina Arnita (BADAN PENERBIT STIEPARI PRESS, 2025)
This study focuses on exploring the impact of the implementation of the e-PADI information system on the PBB-P2 payment process within the Deli Serdang District Revenue Agency. The background of this research is that PBB-P2 revenue collection is still below target. The method used is quantitative with an associative approach through surveys. The respondents in this study are taxpayers residing in Deli Serdang Regency. The sampling technique used is purposive sampling, namely those who have used the e-PADI application in their tax payment process. Data collection was conducted through questionnaires and documentation. The focus of data analysis was on how the e-PADI information system affects the completion of basic and education taxes in rural and urban areas. Based on the findings of this study, the use of the e-PADI information system has a positive impact on the completion of basic and education taxes in rural and urban areas. However, the utilization of this technology is still hindered by various constraints, such as technological limitations and low digital literacy among the community. The research data shows that the e-PADI information system has an impact on PBB-P2 payments, but improvements are still needed in terms of education, socialization, and the quality of digital services.